Heavy metal concentration and potential health risk assessment for the European eel (Anguilla anguilla, Linnaeus 1758) from the Gediz Delta (Eastern Aegean, Türkiye) - Taş Elif Çağrı; Başaran Aslı; Sunlu Uğur; Salman Alp (Oceanological and Hydrobiological Studies)
The present paper is the first document on heavy metal levels in the European eel (Anguilla anguilla) collected from the Gediz Delta in the Eastern Aegean (Türkiye). In this study, concentrations of Cd, Cu, Zn and Pb were determined in the liver, gills, and muscle tissues of A. anguilla eels. Sixty dead eels were obtained between June 2015 and January 2016, and their total size and weight were measured. Heavy metal accumulation levels in edible muscle tissue of the eels were compared with national and international standards, and Estimated Weekly Intake (EWI), Target Hazard Quotient (THQ), and Total Target Hazard Quotient (Σ THQ) were calculated. It was determined that metal concentration levels in A. anguilla follow the sequence of Zn > Cu > Pb > Cd. Zn has the highest concentration in all sampling periods and in all tissue types. It was found that Σ THQ was below 1 and amounted to 0.41. This result shows that there is no carcinogenic risk associated with the consumption of A. anguilla in adults.